Modeling of shear bond in composite slab using interface element - Toh, Yik Fung (2006)
Composite slabs utilizing cold-formed steel decks are widely used in construction industries. The behavior of the slabs is governed by shear bond between concrete and the steel deck. Modeling the shear bond correctly is critical in a numerical study of composite slab. This paper pertains with finite element study to model the shear bond using an interface element available in LUSAS. The interface element normally used for modeling delamination of plane and crack propagation of a composite material was utilized to study the shear bond behavior in composite slab. Experimental data from published literatures was used to verify the finite element analysis results. The results show that with proper assignment of material parameters to the interface elements, the shear bond in the composite slab can be modeled correctly.